Are individual inventors invisible? The missing link between creative people and support for innovation - Šugar, Violeta; Belullo, Alen; Džanić, Emin, ekonomist (2021)
The research about the population of individual inventors/innovators in Croatia was carried out with the aim of finding answers to the following questions: 1. How many inventions/patents in Croatia are (not) commercialized; 2. What are the reasons of (un)successful commercialization of Croatian individual inventors' inventions/patents; 3. Is there any correlation between various forms of support for inventors / patent owners and successful commercialization; 4. Could education/training contribute to the successful commercialization of inventions/patents? The research was designed and carried out on individual inventors/innovators in Croatia via combination of online questionnaire and telephone interviews. The acquired data were analysed by descriptive statistics and nonparametric inferential statistics. Based on the results of the research, the literature and practical experience, a typology of individual inventors / innovators has been created. The research limitations relate to the lack of the institutional data and literature regarding the individual inventors. In addition to practical contribution of the findings regarding the public policies, there is also a theoretical contribution to existing literature.
Istraživanje o populaciji individualnih izumitelja / inovatora u Hrvatskoj provedeno je s ciljem pronalaska odgovora na sljedeća pitanja: 1. koliko izuma/patenata u Hrvatskoj (ni)je komercijalizirano; 2. koji su razlozi (ne)uspješne komercijalizacije izuma/patenata hrvatskih individualnih izumitelja; 3. postoji li korelacija između različitih oblika potpora za izumitelje / vlasnike patenata i uspješne komercijalizacije; 4. može li obrazovanje / edukacija pridonijeti uspješnoj komercijalizaciji izuma / patenata? Istraživanje je kreirano i provedeno na populaciji individualnih izumitelja / inovatora u Hrvatskoj kombinacijom online upitnika i telefonskih intervjua. Prikupljeni su podaci analizirani deskriptivnom i neparametrijskom inferencijalnom statistikom. Temeljem rezultata istraživanja, dostupne literature i praktičnog iskustva kreirana je tipologija individualnih izumitelja / inovatora. Ograničenja provedenog istraživanja povezana su s nedostatkom institucionalnih podataka i literature, koja se rijetko bavi individualnim izumiteljima. Analiza i rezultati imaju teorijski i praktičan doprinos, prvi se odnosi na javne politike, a drugi na proširenje postojećega fonda sekundarnih izvora.
Bibliografija: 37 jed.
Summary ; Sažetak.
Keywords: Inovacije -- Upravljanje inovacijama -- Izumitelji